Otaku Dadakan: Studi Kasus Penggemar Anime One Piece di Kalangan Mahasiswa - Muh. Nur Rahmat Yasim (Emik, 2022)
nime (Japanese animation) which currently become popular in the community has resulted in the emergence of various anime products, such as action figures, posters, comics, and even animated films. One of the most popular anime is One Piece, and its rabid fans are known as anime otaku. This anime otaku phenomenon not only occurs in Japan, but also throughout the world, including Indonesia. This article deals with newcomers who are interested in popular anime, and call themselves otaku, labeled as impromptu otaku by anime otaku. Using a qualitative approach, this research was conducted through social media Instagram and TikTok. The research informants were ten students, who came from public and private universities in the city of Makassar. They consist of six men and four women, whose age range between 19 and 25 years. Data was collected using in-depth interview and observation techniques. One Piece is one of the anime that has a high rating and is the most popular anime of all time. For impromptu otaku, this is considered as “the king of anime", so that fanaticism towards anime is only focused on the One Piece anime, even though there are many other anime that also have high ratings. While anime otaku are not just fans of one anime. In the process of choosing anime One Piece, a person goes through three stages, namely selection, interpretation, and reaction stages. One of the aspects that makes One Piece as an interesting anime for otaku is how One Piece is able to raise spirits through motivational words uttered by certain characters in the One Piece anime. The identity of impromptu otaku is shown through their involvement in various activities, showing that they are fans of One Piece anime, namely following One Piece developments on the internet and social media, collecting One Piece-themed merchandise, and joining the fan community. This indicates that impromptu otaku realizes their "class" when compared to anime otaku. Thus, by participating in related activities they hope to be aligned as anime otaku.